2012
DOI: 10.1111/ppe.12014
|View full text |Cite
|
Sign up to set email alerts
|

Mode of First Delivery and Women's Intentions for Subsequent Childbearing: Findings from the First Baby Study

Abstract: Background More than a dozen studies have reported a reduced rate of childbearing after caesarean delivery (CD). It has been hypothesized that this is because women who deliver by CD are less likely to intend to have subsequent children than women who deliver vaginally -either before childbirth or as a consequence of CD. Little research has addressed either of these hypotheses. Methods As part of an ongoing prospective study, we interviewed 3006 women in their third trimester and 1 month after first childbir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 25 publications
5
85
0
Order By: Relevance
“…There were no significant differences in race/ethnicity (data not shown). Also in the final cohort, there was a greater proportion of non-Hispanic White, higher educated, higher income, and married or cohabitating women than women in the state of Pennsylvania as a whole, which has been noted in prior FBS publications (Kjerulff et al, 2013).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…There were no significant differences in race/ethnicity (data not shown). Also in the final cohort, there was a greater proportion of non-Hispanic White, higher educated, higher income, and married or cohabitating women than women in the state of Pennsylvania as a whole, which has been noted in prior FBS publications (Kjerulff et al, 2013).…”
Section: Resultsmentioning
confidence: 73%
“…Detailed methodology of the FBS is available in prior publications (Kjerulff et al, 2013). To be eligible, women needed to be nulliparous, pregnant with a singleton pregnancy, between the ages of 18 and 35, planning to deliver in a Pennsylvania hospital, able to speak English or Spanish, and willing and able to participate in intermittent interviews for a 3-year period.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…This is consistent with participation studies, where participants tend to be more educated and affluent than the general population. 18,19 Therefore, our results may not be generalized to all U.S. and international populations. Additionally, the study design itself collected breastfeeding information at three points during a 6-month period (2 weeks, 2 months, and 6 months), thus introducing the possibility of recall bias.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, participants in the FBS were more likely to be white non-Hispanic, more educated, older on average, and more likely to have private insurance, as commonly occurs in participation studies. 5,17 Another potential limitation is that most of the FBS participants (92.2%) reported that they intended to breastfeed in the prepartum interview. Although several studies have reported similar rates of breastfeeding intention among American women (92.8% among low-income women in Iowa 18 and 92.0% in a diverse urban population in New York 19 ), most report lower rates of prepartum plans to breastfeed, ranging from 48.2% among women in West Virginia 20 to 83.0% in a national study.…”
Section: Discussionmentioning
confidence: 99%